On the Identity of Sphaenorhynchus platycephalus (Werner, 1894) (Anura: Hylidae) - de Araujo Vieira, Katyuscia (2018)
Sphaenorhynchus platycephalus was briefly described on the basis of a single specimen, with only "S-Amerika" as its locality. Although it has been regarded as a distinct species, compelling evidence is lacking. A comparison of all currently described species of Sphaenorhynchus, including type specimens of several species, allowed us to provide morphological evidence that S. platycephalus and S. orophilus are conspecific, with S. orophilus being a junior synonym of S. platycephalus.